Dosimetric advantages of proton therapy compared with photon therapy using an adaptive strategy in cervical cancer. (2nd July 2016) - van de Schoot, Agustinus J. A. J.; de Boer, Peter; Crama, Koen F.; Visser, Jorrit; Stalpers, Lukas J. A.; Rasch, Coen R. N.; Bel, Arjan
Abstract: Background Image-guided adaptive proton therapy (IGAPT) can potentially be applied to take into account interfraction motion while limiting organ at risk (OAR) dose in cervical cancer radiation therapy (RT). In this study, the potential dosimetric advantages of IGAPT compared with photon-based image-guided adaptive RT (IGART) were investigated. Material and methods For 13 cervical cancer patients, full and empty bladder planning computed tomography (CT) images and weekly CTs were acquired. Based on both primary clinical target volumes (pCTVs) [i.e. gross tumor volume (GTV), cervix, corpus-uterus and upper part of the vagina] on planning CTs, the pretreatment observed full range primary internal target volume (pITV) was interpolated to derive pITV subranges. Given corresponding ITVs (i.e. pITVs including lymph nodes), patient-specific photon and proton plan libraries were generated. Using all weekly CTs, IGART and IGAPT treatments were simulated by selecting library plans and recalculating the dose. For each recalculated IGART and IGAPT fraction, CTV (i.e. pCTV including lymph nodes) coverage was assessed and differences in fractionated substitutes of dose-volume histogram (DVH) parameters (V15Gy, V30Gy, V45Gy, Dmean, D2cc ) for bladder, bowel and rectum were tested for significance (Wilcoxon signed-rank test). Also, differences in toxicity-related DVH parameters (rectum V30Gy, bowel V45Gy ) were approximated based on accumulated dose distributions. Results In 92% (96%) of all recalculated IGAPT (IGART) fractions adequate CTV coverage (V95%  >98%) was obtained. All dose parameters for bladder, bowel and rectum, except the fractionated substitute for rectum V45Gy, were improved using IGAPT. Also, IGAPT reduced the mean dose to bowel, bladder and rectum significantly (p < 0.01). In addition, an average decrease of rectum V30Gy and bowel V45Gy indicated reductions in toxicity probabilities when using IGAPT. Conclusion This study demonstrates the feasibility of IGAPT in cervical cancer using a plan-library based plan-of-the-day approach. Compared to photon-based IGART, IGAPT maintains target coverage while significant dose reductions for the bladder, bowel and rectum can be achieved.